2015
DOI: 10.1089/neu.2014.3808
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Intracerebral Hemorrhage: Risk Factors Associated with Progression

Abstract: The increase in the volume of a traumatic intracerebral hemorrhage (TICH) is a widely studied phenomenon that has a direct impact on the prognosis of patients. The objective of this study was to identify the risk factors associated with the progression of TICH. We retrospectively analyzed the records of 1970 adult patients >15 years of age who were consecutively admitted after sustaining a closed severe traumatic brain injury (TBI) between January 1987 and November 2013 at a single center. Beginning in 2007, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 41 publications
9
77
2
Order By: Relevance
“…It was reported that the increase in the volume of traumatic cerebral hemorrhage occurs in the first few hours after the trauma in 38 to 59% of the cases. Also, the findings in the first non-contrast cranial CT taken after the injury were related to the quality of life score at 12 months after the accident (14,(36)(37)(38). In our study, cranial CT was found to be helpful in the determination of short-term prognosis in CC.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It was reported that the increase in the volume of traumatic cerebral hemorrhage occurs in the first few hours after the trauma in 38 to 59% of the cases. Also, the findings in the first non-contrast cranial CT taken after the injury were related to the quality of life score at 12 months after the accident (14,(36)(37)(38). In our study, cranial CT was found to be helpful in the determination of short-term prognosis in CC.…”
Section: Discussionsupporting
confidence: 50%
“…In patients with trauma, a hemorrhagic contusion is the most common lesion detected on computerized tomography (CT), and in many series, account for approximately % of traumas (2,6,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported HPC as the reason for an operation, sometimes in up to 20% of patients. [3][4][5][6][7][8] Studies have also reported that patients with progression of injury on a repeat CT underwent more frequent interventions related to intracranial pressure management changes, ventriculostomy placement or adjustment, addition of antiseizure medication, repeat CT, intensive care unit observation, delay in extubation, and initiation of thromboprophylaxis, even in patients with stable or improved Glasgow Coma Scale scores. 12,18,[23][24][25] Similarly, Alahmadi et al 18 reported a significant association between radiographic progression of contusions and the need for neurosurgical interventions, even though the mean Glasgow Coma Scale score and mean change in Glasgow Coma Scale score during the hospital course showed no difference.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several authors have reported rates of HPC in 38%-59% of cases. [3][4][5][6][7][8] HPC is a progressive injury that results in irreversible loss of brain tissue with significant increase in morbidity and mortality. 3 Noncontrast head CT is the diagnostic method used to assess patients with hemorrhagic contusions and HPC.…”
mentioning
confidence: 99%
“…We also evaluated the accompanying TBI in all 318 patients. We defined TICH lesions as those with a solid and well-defined appearance and fewer well-defined areas of mixed attenuation5). In well-defined TICH lesions, we measured the baseline volume of the ICH using the formula (A×B×C)/2, where A is the greatest hemorrhage diameter in the CT scan, B is the diameter measured 90 degrees to A, and C is the approximate number of 10-mm CT slices showing hemorrhage19).…”
Section: Methodsmentioning
confidence: 99%